Pelatihan Penguasaan Kosakata Bahasa Inggris Menggunakan Guessing Game bagi Anak-Anak Panti Asuhan Al-Mim Palangkaraya - Nurliana Nurliana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Mastering English vocabulary, which is a foreign language in Indonesia, is not easy. To master English vocabulary, appropriate technique in teaching is needed. This is the basis for carrying out English vocabulary mastery training using guessing game for the children of the Al Mim Palangkaraya Orphanage. This training was attended by ten participants and accompanied by an instructor in March 2023 for one day which included preparation, implementation and evaluation. The training material consists of mastering English vocabulary using guessing game. The list of English vocabulary provided is related to the names of professions in English. The results of the training show that guessing game can be implemented well in the mastering English vocabulary. Guessing game can make the participants motivated, interested, more active, enthusiastic, and not bored. Guessing game can also help the participants to acquire new English vocabulary.